Management Strategy and Development of Pelawan Beach Ecotourism In The Village West Pangke Subsdistrict West Meral District Karimun, Riau Island Province - Veni Amilia Susanti; Hamdi Hamid; Eni Yulinda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted in october 2015 which is housed in The village West Pangke Subsdistrict West Meral District Karimun the Province Riau Islands. This study attempts to: 1) know the state of social, culture and infrastructure tourism on the beach pelawan; 2) know the role of the government and the stakeholders in resource management pelawan coast; 3) studying strategy alternative in the development of tourism on the beach pelawan.Methods used in research it will be a method of surveying.The result showed that the tourism pangke west village of natural tourist set out in tourism pelawan coast.The beach lying along 500 metres form a pattern of crescent. Besides, west village pangke also offers cultural tourism and arts as traditional ceremonies marriage mate, khatam the koran, circumcision accompanied berzanji arts, traditional dance and kompang. But, facilities and the existing infrastructures around the beach pelawan access roads inadequate.In addition to supporting facilities such as hotel, inn, stay home, the restaurant has not available.The government role significantly in the management and tourism development natural as positive support and attitude proactive local government of the local promotions.Based on the evaluation on the environment internal and external, obtained 10 (ten) strength and 6 (six) weakness and 6 (six) opportunities and 6 (six) weakness of parwisata in the river pangke.Based on analysis of the training or priority strategy with three the first namely: (1) do management and development of cultural tour and nautical (ecotourism); (2) promoting local tourist; and (3) facility development also advocates tourism.Keywords: ecotourism, SWOT, strategy, Pelawan Beach